2011
DOI: 10.1038/aps.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ticlopidine on pharmacokinetics of losartan and its main metabolite EXP-3174 in rats

Abstract: npg IntroductionLosartan (DuP 753,, an angiotensin II receptor antagonist, has a low side-effect profile and is approved for the treatment of hypertension, alone or in combination with other agents [1] . After oral administration, losartan is almost completely absorbed and extensively metabolized to a carboxylic acid derivative, EXP-3174, mainly by cytochrome P450 (CYP) 2C9 and 3A4 [2] . EXP-3174 is a major active metabolite in both rats and humans and is a more potent inhibitor of angiotensin II receptor than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
(26 reference statements)
0
8
0
Order By: Relevance
“… 78 According to in vitro studies, E-3174 is also formed by the action of CYP3A4, 79 , 80 but in vivo studies with therapeutic doses of losartan showed no significant contribution to losartan CYP3A4 metabolism. 81 The predominant contribution of CYP2C9 to losartan metabolism was confirmed indirectly by a decrease in the AUC of E-3174 when it was used in combination with moderate inhibitor CYP2C9 (fluconazole), while no change in AUC of E-3174 was observed when losartan was used in combination with a strong CYP3A4 inhibitor (itraconazole). 47 In many studies, losartan has been safely used as a marker substrate for phenotyping CYP2C9 activity.…”
Section: Prediction Of Impact Of Drugs On Cyp Isoenzymes In Vivomentioning
confidence: 99%
“… 78 According to in vitro studies, E-3174 is also formed by the action of CYP3A4, 79 , 80 but in vivo studies with therapeutic doses of losartan showed no significant contribution to losartan CYP3A4 metabolism. 81 The predominant contribution of CYP2C9 to losartan metabolism was confirmed indirectly by a decrease in the AUC of E-3174 when it was used in combination with moderate inhibitor CYP2C9 (fluconazole), while no change in AUC of E-3174 was observed when losartan was used in combination with a strong CYP3A4 inhibitor (itraconazole). 47 In many studies, losartan has been safely used as a marker substrate for phenotyping CYP2C9 activity.…”
Section: Prediction Of Impact Of Drugs On Cyp Isoenzymes In Vivomentioning
confidence: 99%
“…The inhibitory effect of licochalcone A (IC 50 = 5.9 μM) on CYP3A4 was weaker than that of ketoconazole (IC 50 = 0.1 μM) externally. In general, when the inhibitory effect (IC 50 ) of CYP3A4 was below 20 μM, the bioavailability (AUC) of CYP3A4 substrates were increased by only CYP3A4 inhibitors [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“… 2008 ; Yang et al. 2011 ). Losartan is mainly metabolized by cytochrome P450 enzymes CYP3A4 and CYP2C9, and therefore, modulation of CYP3A4 or CYP2C9 activities may cause significant changes in the pharmacokinetic profiles of losartan and its active metabolite EXP3174 (Li et al.…”
Section: Introductionmentioning
confidence: 99%